With Great Power Comes Great Pedagogy: Teaching, Learning, and Comics, Susan E. Kirtley, Antero Garcia and Peter E. Carlson (eds) (2020). Issue 1 (1st July 2020) - DeHart, Jason D.
With Great Power Comes Great Pedagogy: Teaching, Learning, and Comics, Susan E. Kirtley, Antero Garcia and Peter E. Carlson (eds) (2020)Jackson, MS: University Press of Mississippi, 270 pp., ISBN 978-1-49682-605-3, p/bk, $30